Lattice Boltzmann simulation of ice droplet melting process and motion behavior in gas diffusion layer of proton exchange membrane fuel cell under thermal purging - Xu, Sheng (2024)
In order to explore the melting and motion process of ice droplets in the gas diffusion layer of proton exchange membrane fuel cell under thermal purging, this paper developed a numerical calculation model using the lattice Boltzmann method. The effects of the Reynolds number, Stefan number, and solid-liquid interface force coefficient were then studied. Finally, a scaling analysis of melting rate and Fourier number was performed. The results demonstrated that at the beginning of the thermal purging process, part of the heat is blown towards the ice droplets, causing them to start melting. The droplets then gradually move towards the low-pressure area. Eventually, the liquid water moves out of the gas diffusion layer. The increase of the Reynolds number leads to the rapid increase of the temperature and melting rate. In addition, when the Stefan number increases, an ice droplet melts and moves faster, the velocity in the horizontal direction rapidly decreases, and the temperature increases. When the solid-liquid interface force coefficient increases, the gas-liquid interface at the top of water becomes concave downward. The solid-liquid interface force coefficient has little effect on the ice melting rate.